Impact of Differential Densification on the Pore Structure of Tight Gas Sandstone: Evidence from the Permian Shihezi and Shanxi Formations, Eastern Sulige Gas Field, Ordos Basin, China. (21st March 2019) - Wang, Meng; Tang, Hongming; Tang, Haoxuan; Liu, Shu; Zhang, Liehui; Zeng, Ming; Cheng, Yulin
Abstract : The tight sandstone reservoirs of the Permian Shihezi and Shanxi Formation with strong heterogeneity constitute the main producing zone of the eastern Sulige gas field. The process of differential densification results in various reservoir qualities. Mineral composition, structural characteristic, pore system, and diagenesis were investigated with analyses of well logs, thin sections, porosity, and horizontal permeability of the core plugs; environmental scanning electron microscopy (ESEM); nuclear magnetic resonance (NMR); X-ray computed tomography (X-CT); and fluid inclusion homogenization temperature. The results show that lithic sandstone reservoirs experienced complex and various diagenetic evolutions. Eight types of densification modes can be divided according to the diagenesis paths; these modes represent lithofacies with different densification times and reservoir qualities. Intense mechanical compaction is the main reason for the formation of lithofacies 1, 2, and 5. Lithofacies 4, 6, and 7 formed due to intense cementation, increasing the impermeability of the diagenetic system. The primary pore space in lithofacies 3 is preserved due to the overpressure and chlorite coatings. The dissolution and weak cementation of lithofacies 8 contribute to reservoir development. The middle-lower part of braided channel lags and channel bars, the middle part of meandering riverbed lags, and the middle part of point bars are favourable for reservoir development.